Reflective learning and teaching in primary schools - Hansen, Alice (Sage Publications, 2017)
As a trainee teacher, you are expected to demonstrate reflective practice in many ways throughout your course. -- Reflective Learning and Teaching in Primary Schools provides focused support, enabling you to demonstrate your ability to be meaningfully reflective. It considers how to encourage children to be reflective in their learning and how to be analytical with regards to your own practice, ultimately helping you to improve learning and teaching. -- Editor Alice Hansen includes a chapter on reflective journals with practical guidance on how to approach them, and covers children's voice and coaching as tools for reflection. Features case studies and interactive activities, helping you link theory to practice
Keywords: Reflective learning -- Great Britain; Reflective teaching -- Great Britain; Education, Elementary -- Great Britain; Grundschulunterricht; Großbritannien; Aufsatzsammlung